Surgical left subclavian artery revascularization for thoracic aortic stent grafting: a single-centre experience in 101 patients. (28th February 2018) - van der Weijde, Emma; Saouti, Nabil; Vos, Jan Albert; Tromp, Selma C; Heijmen, Robin H
Abstract: OBJECTIVES: To evaluate the indications, perioperative strategy and postoperative outcome of surgical left subclavian artery (LSA) revascularization combined with thoracic endovascular aortic repair (TEVAR) covering the LSA. METHODS: Between 2000 and 2017, a total of 101 consecutive patients underwent surgical revascularization of the LSA prior to, concomitant or following TEVAR. Revascularization was performed through a small supraclavicular incision and consisted of a transposition or bypass graft, using intraoperative transcranial Doppler monitoring. Data regarding indication, procedural details and postoperative results were retrospectively analysed. RESULTS: In total, 63 subclavian–carotid bypass grafts and 38 subclavian–carotid transpositions were performed in the context of TEVAR. The majority was performed prior to stent grafting to reduce the risk of stroke ( n  = 50), spinal cord ischaemia ( n  = 20), left arm malperfusion ( n  = 10) or to preserve a patent left internal mammary artery coronary bypass graft ( n  = 2). Secondary revascularization was performed in 14 patients, 2 times immediately due to acute left arm malperfusion and 12 times to treat invalidating left arm claudication. No in-hospital mortality and permanent spinal cord ischaemia occurred. Two (2%) ischaemic strokes were observed in patients with concomitant procedures, and none when separate, staged procedures were performed. Additional complications observed were permanent peripheral nerve palsies (9%), chyle leakage requiring diet (6%) and 1 bypass occlusion requiring a redo procedure. CONCLUSIONS: In patients predominantly selected upon the anticipated risk of (posterior) stroke, spinal cord ischaemia and left arm malperfusion, surgical revascularization of the LSA proved to be a safe treatment option to preserve antegrade LSA flow in the context of TEVAR.